Beneficiation of Rutile Ore by combined agglomeration and flotation methods - Bilgin, Öykü; Sakcalı, Alaattin (My University, 2013)
Titanium known as a rare element is the most abundant sixth element in the earth crust. Titanium tend to be precious, due to its rare ore concentration and obtaining from metal ore. Most of ore is used TiO2 (titanium oxide) form. Titanium oxide is known as white painting material. Apart from that it is also widely used in many fields such as cosmetic industry, linoleum (cerecloth), synthetic silk, white ink, colored glass, ceramic glaze, leather and cloth dyeing, welding rod construction and paper industry. TiO2 is obtained from titanium ores, sulphate and chloride methods. The old sulphate method produces a lot of environmental pollution. On the other hand, Chloride method requires very high graded ores. As for titanium beneficiation methods, flotation, gravity beneficiation, magnetic separation and beneficiation via electrostatic separation methods are used. Rutile is the most important titanium mineral. It is considered that the most important titanium reserves in Turkey are in Manisa with 1.11% TiO2 tenor and 1.272.000 ton, total reserves are 100 million ton with 0.5-1% TiO2 tenor. Rutile samples used in this study were taken from region Manisa-Alasehir. Rutile samples with -106 μm grain size were subjected to agglomeration and flotation together with using different pH and reactives. According to the test results, the highest TiO2% tenor was obtained with 11.90% value in pH: 4, the highest recovery was obtained with 79% value in pH: 7.
Keywords: Agglomeration; Froth flotation; Industrial minerals; Optimization; Titanium